Ganoboninketal C from Ganoderma boninense improves the efficacy of CDDP-based chemotherapy through inhibiting translesion DNA synthesis - Xiaolu Ma; Fei Yang; Ke Ma; Hongyan Shen; Junjie Han; Kai Wang; Yeran Yang; Jiawei Zhu; Ruiyuan An; Qilin Wang; Tie-Shan Tang; Bo Zhou; et al. (Food Science and Human Wellness)
Translesion DNA synthesis (TLS) can bypass DNA lesions caused by chemotherapeutic drugs, which usually result in drug resistance. Given its key role in mutagenesis and cell survival after DNA damage, inhibition of the TLS pathway has emerged as a potential target for improving the efficacy of DNA-damaging agents such as cisplatin (CDDP), a widely used anticancer agent. Unfortunately, few suitable natural TLS inhibitors have been reported. Here, we found that a triterpenoid compound Ganoboninketal C (26-3) from Ganoderma boninense, a traditional Chinese medicine, can impair CDDP-induced TLS polymerase eta (Polη) focus formation, PCNA monoubiquitination as well as mutagenesis. Moreover, 26-3 can significantly sensitize tumor cells to CDDP killing and reduce the proportion of cancer stem cells in AGS and promote apoptosis after CDDP exposure. Interestingly, 26-3 can also sensitize tumor cells to Gefitinib therapy. Mechanistically, through RNA-seq analysis, we found that 26-3 could abrogate the CDDP-induced upregulation of Polη and PIDD (p53-induced protein with a death domain), 2 known factors promoting TLS pathway. Furthermore, we found that activating transcription factor 3 is a potential novel TLS modulator. Taken together, we have identified a natural TLS inhibitor 26-3, which can be potentially used as an adjuvant to improve clinical efficacy.